Migrant Illegality, Nation Building, and the Politics of Regularization in Canada - McDonald, Jean (Refuge: Canada’s Journal on Refugees, 2011)
Regularization, a means for people living with precarious immigration status to legalize or “regularize” their status, is a central demand of immigrant rights groups across Canada. From a perspective of No Borders, does the demand for regularization, while challenging the day-to-day practices of Citizenship and Immigration Canada, also unintentionally reinforce state power? Historical research on regularization programs in Canada suggests that regularization programs do not eliminate migrant illegality but reconfigure it. In this way, regularization may be implicated in processes that both makes and unmakes illegality within the context of immigration and citizenship in Canada.